Impact of GEM parboiling technique on women’s income and food security in Mali - Suh, Neville; Diallo, Aboubacar; Dossou-Yovo, E.R (2024)
The AICCRA Mali project focuses on building the capacity of both women and men to accelerate the adoption of climate adaptation strategies. A total of 250 participants (237 females and 13 males) were trained on the GEM parboiling process, a climate-friendly technique for processing rice. The study examined the impact of adopting the GEM parboiler on livelihoods and identified key drivers influencing its adoption. The results revealed that adopters of the GEM parboiler experienced a 24,276 FCFA increase in income per hectare compared to non-adopters. Factors positively influencing women’s adoption of the GEM parboiler included their years of schooling, the number of household members, and assistance from household members in GEM parboiling activities. These findings emphasize the importance of engaging women in climate adaptation initiatives through capacity building to improve household income and food security.